Sustainable Fashion Education in changing World Scenario - Agarwal, Vishaka (European Journal of Sustainable Development, 2018)
With the changing world scenario, information technology is hitting all walks of life , the globalised phenomenon along with alarming environmental concerns have led the world to innovate ways and methods to address various concerns in a sustainable way. Fashion education also needs to undergo change in its pedagogy and develop newer knowledge source and materials which are eco-friendly ,leaving less carbon footprints on the earth .The fashion Education curriculum needs to have more “Free Thinking” orientation and interaction and information of technological advances of materials and processes which consume less energy and less waste post production. Looking at current trends, the future would require Fashion Designers to have multidisciplinary knowledge of Design, Technology and managerial skills to evolve and compete in the Fashion Industry. Questionnaire would be made to collect the perception from Fashion experts, professionals, Academia and students to assess the kind of knowledge they would like to be incorporated in the Fashion curriculum which has sustainable concepts incorporated in keeping tandem with the future trends. Keywords: Fashion , Curricula , Sustainable, Education